2016
DOI: 10.1002/brb3.511
|View full text |Cite
|
Sign up to set email alerts
|

Striatal morphology correlates with frontostriatal electrophysiological motor processing in Huntington's disease: an IMAGE‐HD study

Abstract: BackgroundHuntington's disease (HD) causes progressive atrophy to the striatum, a critical node in frontostriatal circuitry. Maintenance of motor function is dependent on functional connectivity of these premotor, motor, and dorsolateral frontostriatal circuits, and structural integrity of the striatum itself. We aimed to investigate whether size and shape of the striatum as a measure of frontostriatal circuit structural integrity was correlated with functional frontostriatal electrophysiological neural premot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
(152 reference statements)
2
4
0
Order By: Relevance
“…Consistent with previous studies, significant differences in striatal shape metrics were observed between individuals with pro-HD and HC 26 , 27 . In particular, individuals with pro-HD displayed significant shape deflation in comparison with HC that was more evident for the right hemispheres of the putamen and caudate than for the left.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies, significant differences in striatal shape metrics were observed between individuals with pro-HD and HC 26 , 27 . In particular, individuals with pro-HD displayed significant shape deflation in comparison with HC that was more evident for the right hemispheres of the putamen and caudate than for the left.…”
Section: Discussionsupporting
confidence: 91%
“…Together, these findings highlight the inherent variability in motor features across individuals with pro-HD, which has been well-documented in previous epidemiological studies and is presumed to relate to differences in striatal pathology, genetic burden, lifestyle and genetic modifiers, which could be the subject of future investigations. Consistent with previous studies, significant differences in striatal shape metrics were observed between individuals with pro-HD and HC 26,27 . In particular, individuals with pro-HD displayed significant shape deflation in comparison with HC that was more evident for the right hemispheres of the putamen and caudate than for the left.…”
Section: Discussionsupporting
confidence: 91%
“…This could involve atrophy of brain areas that is increased with age in HD patients. Previous studies revealed that HD, which typically presents between 35 and 45 years of age [34], could cause progressive atrophy in the striatum [35]. Even in prodromal and early symptomatic HD, putamen atrophy rates of about 2.3% per year and 4.5% per year, and caudate atrophy rates of 1.1%-2.4% per year and 2.9%-4.9% per year, respectively, have been reported in comparisons to controls [36][37][38].…”
Section: Agementioning
confidence: 98%
“…Even in a clearly genetic disorder, great effort has been made into defining a clinical phenotype encompassing the prodromal period through to the development of neurological and psychiatric features. For example, there has been evidence that compensatory motoric electrophysiologic processes in HD are correlated with the structural integrity of neurocircuits serving these functions (Turner et al, 2016). The development of such multi-level pathophysiologic measures may lead to the better characterisation of endophenotypes, such as corticostriatal circuit dysfunction leading to cognitive, motoric and emotional manifestations.…”
Section: Aetiology Pathophysiology and Endophenotypes In Neuropsychimentioning
confidence: 99%